Effects of Cognitive Status on Life Participation of Cancer Survivors - Mary F. Baxter PhD, OT, FAOTA; Theresa Smith PhD, OTR/L, CLVT; Jennifer Wahowski, OTR (Scholarworks @ WMU, 2014)
The purposes of this study were to identify the cognitive status of cancer survivors, determine the effect of cognitive status on function and participation in daily activities, and explore how cancer survivors perceive changes in their cognition. The study used a quantitative nonexperimental cross-sectional design. The participants included 35 cancer survivors from two different sites. Instruments included the Montreal Cognitive Assessment (MoCA) and the Reintegration to Normal Index-Postal Version (RNLI-P) in the measurement of cognitive impairment and functional performance respectively. Data were also collected with a supplemental questionnaire to explore participants' perspectives on their cognitive difficulties and current function. The participant scores on the MoCA indicated cognitive impairment (μ= 25) and their scores on the RNLI-P demonstrated subpar reintegration (μ=9.64). Twenty-one participants answered the supplemental questionnaire. In content analysis of questionnaire responses, 17/21 participants reported some level of cognitive change related to cancer and cancer treatment. Data from an open-ended question were organized into four categories: decreased participation, more selective in activities, balance in activities, and cognitive changes. Study results indicate a large percentage of cancer survivors demonstrate mild cognitive impairment as well as changes in participation in instrumental activities of daily living.